Pemanfaatan Digital Marketing dalam Promosi Pariwisata pada Era Industri 4.0 - I Gede Agus Krisna Warmayana (UHN IGB Sugriwa Denpasar, 2018)
Digital marketing is promoting online can use website and mobile media. In industry 4.0 is an automatic trend to carry out activities in the business field. The use of digital marketing in the industrial era 4.0 in the world of tourism is very influential supported by 5 digital marketing applications, namely websites, online advertising, social media, web forums and mobile applications. By applying digital marketing tourism will grow professionally and globally.